Biometric characterization of Campomanesia xanthocarpa (Mart.) O. Berg. in an araucaria forest - Isabel HomczinskI; Afonso Figueiredo Filho; Fabiane Aparecida de Sousa Retslaff; Andrea Nogueira Dias; Ana Paula Micali Figueiredo; Aparecida Juliana Martins Corrêa; Jocasta Lerner (Acta Biológica Catarinense, 2017)
The present research aimed to analyze biometric characteristics of Campomanesia xanthocarpa and its fruits and its fruit yield. This study was developed in araucaria forest at Irati National Forest, Paraná state. To perform this analysis, 31 individuals were selected and the total height and commercial height, diameter breast height (DBH), crown diameter, crown length, crown proportion, crown formal, salience index, range index and slenderness rate were measured. From the fruits, variables as length, width, weight and number of seeds per fruit were measured. The fruit yield was estimated by means of the fruit number per branch and the average fruit weight per tree. The species presented total height, DBH and crown diameter of 14.2 m, 32.09 cm and 9.5 m, respectively. The crown diameter is 30 times greater than DBH, and 49.71% from total height is occupied by its crown. The fruits presented 22.01 mm, 19.74 mm, 6.64 g and eight units for width, length, weight and seeds/fruit, respectively. The yield was 1.273 fruits, with 8.64 kg.tree-1. The species presents slow growth, with slender crown and resistance to weathering. Its fruits had great potential for selection for commercialization.